The Influence of Student Perceptions on Learning Outcomes in the Food Microbiology Course - Ismail, Ismail; Madee, Punya (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to determine the description of students' perceptions of the Food Microbiology course, analyze students' learning outcomes in the course, and identify the influence of students' perceptions on learning outcomes to provide a basis for developing more effective learning strategies in higher education environments. Methodology: This study employed a quantitative approach with a survey method. The research instruments consisted of a Likert-scale questionnaire and documentation of learning outcome scores. The sampling technique used simple random sampling. Data analysis was performed using descriptive statistics, the Kolmogorov-Smirnov normality test, ANOVA linearity test, Product Moment correlation, and simple linear regression using IBM SPSS Statistics software. Main Findings: Student perceptions of the Food Microbiology course were moderate, while student learning outcomes were generally good. The research data were normally distributed and met the linearity assumption. Correlation analysis showed a strong relationship between student perceptions and learning outcomes. Simple linear regression results indicated that student perceptions significantly influenced learning outcomes in the Food Microbiology course. Novelty/Originality of this study: The novelty of this research lies in its empirical analysis of the influence of student perceptions on learning outcomes, specifically in Food Microbiology courses, a topic rarely studied. This research provides a novel contribution to understanding the importance of student perceptions as a determinant of academic success and serves as a basis for developing more contextual and effective learning strategies.